Aerobic Denitrification and Heterotrophic Sulfur Oxidation in the Genus Halomonas Revealed by Six Novel Species Characterizations and Genome-Based Analysis - Wang, Liping; Shao, Zongze (Frontiers in Microbiology, 2021)
Bacteria of Halomonas are widely distributed in various environments and play a substantial role in the nutrient cycle. In this report, 14 strains capable of aerobic denitrification and heterotrophic sulfur oxidation were isolated from different habitats. Based on the phenotypic, genotypic, and chemotaxonomic analyses, these strains were considered to represent six novel species of the genus Halomonas, for which the names Halomonas zhangzhouensis sp. nov. type strain CXT3-11T (= MCCC 1A11036T = KCTC 72087T), Halomonas aerodenitrificans sp. nov. CYD-9T (= MCCC 1A11058T = KCTC 72088T), Halomonas sulfidoxydans sp. nov. CYN-1-2T (= MCCC 1A11059T = KCTC 72089T), Halomonas ethanolica sp. nov. CYT3-1-1T (= MCCC 1A11081T = KCTC 72090T), Halomonas sulfidivorans sp. nov. NLG_F1ET (= MCCC 1A13718T = KCTC 72091T), and Halomonas tianxiuensis sp. nov. BC-M4-5T (= MCCC 1A14433T = KCTC 72092T) are proposed. Intriguingly, they formed a unique group with 11 other species designated as the “H. desiderata group.” To better understand their featured metabolisms, genes involved in denitrification and sulfur oxidation were analyzed, along with 193 other available genomes of the whole genus. Consistently, complete denitrification pathways were confirmed in the “H. desiderata group,” in which napA, narG, nirS, norB, and nosZ genes co-exist. Their nitrite reductase NirS formed a unique evolutionary lineage, distinguished from other denitrifiers in Halomonas. In addition, diverse occurrence patterns of denitrification genes were also observed in different phylogenetic clades of Halomonas. With respect to sulfur oxidation, fccAB genes involved in sulfide oxidation commonly exist in the “H. desiderata group,” while sqr genes are diverse and can be found in more species; sqr genes co-occurred with fccAB in eight strains of this study, contributing to more active sulfide oxidation. Besides, the tsdA gene, which encodes an enzyme that oxidizes thiosulfate to tetrathionate, is ubiquitous in the genus Halomonas. The widespread presence of sqr/fccAB, pdo, and tsdA in Halomonas suggests that many Halomonas spp. can act as heterotrophic sulfur oxidizers. These results provide comprehensive insights into the potential of denitrification and sulfur oxidation in the whole genus of Halomonas. With regard to the global distribution of Halomonas, this report implies their unneglectable role in the biogeochemical cycle.